Poly(2-hydroxyethyl methacrylate)-quercetin Conjugate as Biomaterial in Ophthalmology: An “ab initio” Study - Manuela Curcio; Giuseppe Cirillo; Ortensia Ilaria Parisi; Francesca Iemma; Umile Gianfranco Spizzirri; Ilaria Altimari; Nevio Picci; Francesco Puoci (Journal of Functional Biomaterials, 2011)
A novel polymeric material with antioxidant properties and suitable for ophthalmic application was synthesized by free radical grafting reaction between 2-hydroxyethyl methacrylate and quercetin. The presence of quercetin in the polymeric chain was confirmed by FT-IR and UV-Vis analyses, while an estimation of the amount of quercetin bound per gram of polymer was obtained by the Folin-Ciocalteu assay. The conjugate shows high biocompatibility (HET-CAM assay) and antioxidant and anti-inflammatory properties which were extensively investigated by specific in vitro tests.